2017
DOI: 10.1152/ajprenal.00643.2016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial colony-forming cells ameliorate endothelial dysfunction via secreted factors following ischemia-reperfusion injury

Abstract: Damage to endothelial cells contributes to acute kidney injury (AKI) by leading to impaired perfusion. Endothelial colony-forming cells (ECFC) are endothelial precursor cells with high proliferative capacity, pro-angiogenic activity, and in vivo vessel forming potential. We hypothesized that ECFC may ameliorate the degree of AKI and/or promote repair of the renal vasculature following ischemia-reperfusion (I/R). Rat pulmonary microvascular endothelial cells (PMVEC) with high proliferative potential were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 72 publications
(74 reference statements)
2
48
0
1
Order By: Relevance
“…Administration of ECFCs also significantly attenuated increases in plasma creatinine, tubular necrosis, macrophage infiltration, oxidative stress, and apoptosis in the rodent AKI model (51). Similar effects were recently reported when rodent HPP-ECFC or human CB-ECFC were intravenously injected into rodents with AKI; furthermore, the preventative functions were present in paracrine factors secreted by the rodent and human ECFC (52). Other reports agree that the beneficial effects of ECFCs in preventing AKI damage to kidneys may not require cell engraftment (53), but do require ECFC-derived exosomes (51).…”
Section: Kidneysupporting
confidence: 78%
“…Administration of ECFCs also significantly attenuated increases in plasma creatinine, tubular necrosis, macrophage infiltration, oxidative stress, and apoptosis in the rodent AKI model (51). Similar effects were recently reported when rodent HPP-ECFC or human CB-ECFC were intravenously injected into rodents with AKI; furthermore, the preventative functions were present in paracrine factors secreted by the rodent and human ECFC (52). Other reports agree that the beneficial effects of ECFCs in preventing AKI damage to kidneys may not require cell engraftment (53), but do require ECFC-derived exosomes (51).…”
Section: Kidneysupporting
confidence: 78%
“…In mice with ischemic AKI, intravenous administration of ECFC significantly attenuated increases in plasma creatinine, tubular necrosis, macrophage infiltration, oxidative stress and apoptosis, without cell engraftment in the kidneys ( 77 ). Administration of ECFC conditioned media or ECFC-derived exosomes also exerted a protective effect, indicating that the effects of cord blood ECFC are due to ECFC-derived exosomes ( 77 , 78 ). Further studies demonstrated that ECFC exosomes were enriched in miR-486-5p, which targets the phosphatase and tensin homolog (PTEN) ( 79 ).…”
Section: Ecfc For Autologous Cell Therapy For Vascular Repairmentioning
confidence: 97%
“…ECFC cell therapy might also exert a therapeutic effect in acute kidney injury (AKI). Preclinical models have shown that use of ECFC can mitigate the severity of disease and preserve vascular function ( 77 , 78 , 99 , 100 ). In most studies the effect is mediated by secreted factors from ECFC and not cell engraftment.…”
Section: Ecfc For Autologous Cell Therapy For Vascular Repairmentioning
confidence: 99%
“…first described the isolation of “endothelial progenitor cells” (EPCs) from human peripheral blood in 1997, and showed that these cells express endothelial cell surface markers and promote neovascularization 3 . Subsequent animal studies revealed that administration of EPCs exerts protective effects in AKI 4 6 , hindlimb ischemia 7 , and ischemic retinopathy 8 . Homing of progenitor cells to sites of ischemia appears to play an important role in mediating the protective effects, and could involve cell surface B1 and B2 integrin expression, the G protein-coupled receptor C-X-C chemokine receptor type 4 (CXCR4), and interaction with chemokines such as stromal cell-derived factor (SDF)-1α 9 11 .…”
Section: Introductionmentioning
confidence: 99%